1999
DOI: 10.1089/088922299311132
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Human Immunodeficiency Virus Type 2 Subtype B in Abidjan, Ivory Coast

Abstract: We analyzed the genetic variability and phylogenetic relationships among 28 HIV-2 strains collected from patients enrolled in an HIV epidemiologic study in Abidjan, Ivory Coast, during 1995-1996. Although both subtype A (n = 8; 29%) and subtype B (n = 20; 71%) were present in this sampling, the majority of infections were caused by subtype B viruses. These findings contrasted with the reported predominance of HIV-2 subtype A in other African countries. The broad genetic diversity identified among protease gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 20 publications
3
33
0
Order By: Relevance
“…Analysis of primary PBMC from 10 HIV-2-infected individuals revealed that DNA of those from 8 was amplified by using these primers (Table 2), giving an amplification efficiency of 80%. These results are comparable to those for the primers identified in the protease region, which are highly specific for HIV-2 detection only (26).…”
Section: Resultssupporting
confidence: 76%
“…Analysis of primary PBMC from 10 HIV-2-infected individuals revealed that DNA of those from 8 was amplified by using these primers (Table 2), giving an amplification efficiency of 80%. These results are comparable to those for the primers identified in the protease region, which are highly specific for HIV-2 detection only (26).…”
Section: Resultssupporting
confidence: 76%
“…This is not surprising for HIV-2 group B, since the great majority of group B infections have been identified in Côte d'Ivoire and neighboring countries to the east (34,54). By contrast, HIV-2 group A is prevalent throughout west Africa (17,23,51).…”
Section: Sivsmm Infection Seems Nonpathogenic In Its Natural Hostmentioning
confidence: 99%
“…In the case of HIV-1, infections with groups N and O have been largely confined to Gabon and Cameroon (4,5,42), while group M has spread pandemically (51,52). In the case of HIV-2, groups A and B have infected substantial numbers of people in west Africa (17,23,34,54,79), while groups C to H have each been identified only in single individuals (14,18,22,76). Circumstances that favored cross-species transmission and subsequent amplification of only a subset of these viruses are unknown but have implications for potential future SIV transmissions.…”
mentioning
confidence: 99%
“…PR gene sequencing was performed retrospectively on available plasma specimens collected between 1994 and 2001 and stored at Ϫ80°C. HIV-2 RNA was extracted from 1 ml of plasma, and the PR gene was amplified from 10 l of RNA and sequenced as previously described (18). Sequence alignments were performed with Sequence Navigator software, and sequences were compared to HIV-2 clade A and B consensus sequences (Los Alamos database: http://hiv-lanl.gov) (15).…”
mentioning
confidence: 99%